2007
DOI: 10.1002/nbm.1144
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of complementary spatial modulation of magnetization tagging in the rat heart after manganese injection

Abstract: It has been shown that manganese-enhanced MRI (MEMRI) can safely depict the myocardial area at risk in models of coronary occlusion-reperfusion for at least 2 h after reperfusion. To achieve this, a solution of MnCl(2) is injected during coronary occlusion. In this model, the regional function quantification deficit of the stunning phase cannot be assessed before contrast injection using MR tagging. The relaxation effects of manganese (which remains in normal cardiac myocytes for several hours) may alter the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
(24 reference statements)
1
9
0
Order By: Relevance
“…That study also reported, in accordance with our findings, prominent heterogeneity in the Sc in healthy rat hearts. Our results are also in excellent agreement with other studies on global myocardial Sc in rat hearts [32,33]. …”
Section: Discussionsupporting
confidence: 93%
“…That study also reported, in accordance with our findings, prominent heterogeneity in the Sc in healthy rat hearts. Our results are also in excellent agreement with other studies on global myocardial Sc in rat hearts [32,33]. …”
Section: Discussionsupporting
confidence: 93%
“…No correlation was found, either for sham, or for control groups due to the lack of dispersion of wall thickening and normalized signal intensity values. However, even if these results depicted the contraction deficit relative to infarction, an important improvement in function evaluation would be to perform assessment of intramyocardial strains, either by displacement-encoded imaging with stimulated echos (DENSE) (34) or with myocardial tagging, as was previously reported in rat myocardium (35) and also in mice (36,37). Moreover, it has been shown that myocardial tagging can also provide accurate EF measurement (38), so both regional and global function can be acquired in one single acquisition.…”
Section: Function Assessmentmentioning
confidence: 97%
“…Luciferase‐transfected hESC (hESC‐luc + , H9 WiCell Distribution Lot, National Stem Cell Bank c/o WiCell Research Institute, Madison, WI) was employed for this experiment (courtesy of Dr. Joseph Wu) (15). These cells were maintained using one of two feeder systems: 1) irradiated mouse embryonic fibroblasts (mEF) feeder layer with hESC growth media (80% knockout Dulbecco modified Eagle medium [Invitrogen, Carlsbad, CA], 20% serum replacement [Invitrogen], 0.1 mM 2‐mercaptoethanol [Sigma, St. Louis, MO], 0.1 mM nonessential amino acids [Invitrogen], 1% penicillin/streptomycin [Invitrogen], 2 mM L‐glutamine [Invitrogen] with rh‐bFGF [R&D Systems, Minneapolis, MN] 4 ng/mL), and 2) growth factor reduced Matrigel (BD Biosciences, San Jose, CA) without mEF feeder layer using growth media described above and higher concentration of rh‐bFGF (20 ng/mL).…”
Section: Methodsmentioning
confidence: 99%